Associations between stool micro-transcriptome, gut microbiota, and infant growth. (7th December 2021) - Carney, Molly C.; Zhan, Xiang; Rangnekar, Akanksha; Chroneos, Maria Z.; Craig, Sarah J.C.; Makova, Kateryna D.; Paul, Ian M.; Hicks, Steven D.
Abstract: Rapid infant growth increases the risk for adult obesity. The gut microbiome is associated with early weight status; however, no study has examined how interactions between microbial and host ribonucleic acid (RNA) expression influence infant growth. We hypothesized that dynamics in infant stool micro-ribonucleic acids (miRNAs) would be associated with both microbial activity and infant growth via putative metabolic targets. Stool was collected twice from 30 full-term infants, at 1 month and again between 6 and 12 months. Stool RNA were measured with high-throughput sequencing and aligned to human and microbial databases. Infant growth was measured by weight-for-length z -score at birth and 12 months. Increased RNA transcriptional activity of Clostridia ( R = 0.55; Adj p = 3.7E-2) and Burkholderia ( R = −0.820, Adj p = 2.62E-3) were associated with infant growth. Of the 25 human RNAs associated with growth, 16 were miRNAs. The miRNAs demonstrated significant target enrichment (Adj p < 0.05) for four metabolic pathways. There were four associations between growth-related miRNAs and growth-related phyla. We have shown that longitudinal trends in gut microbiota activity and human miRNA levels are associated with infant growth and the metabolic targets of miRNAs suggest these molecules may regulate the biosynthetic landscape of the gut and influence microbial activity.